Supplementary Feeding: Effect on Growth and Blood Metabolites in Sahiwal Heifers - Narvariya, D.S.; Chandra, Ramesh; Kumar, Nishant; Roy, A.K.; Datt, Chander; Mehla, R.K. (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to evaluate the effect of provision of 25% extra concentrate mixture over and above the NRC recommendation on body growth and blood metabolite levels in Sahiwal heifers. The average daily body weight gain was higher (P<0.05) by 26% in group T2 compared to group T1 (501.42 vs. 398.56 g) and the former group showed better feed conversion ratio (10.97 vs. 12.86 kg feed consumed/kg gain). The DM intake (5.11 vs. 5.39 kg/d) was 5.48% higher in group T2 compared to group T1. The supplementary feeding resulted in increased (P<0.05) in body length, heart girth and paunch girth in group T2 compared to group T1 whereas no significant difference (P<0.05) was observed with regards to changes in height at withers. The concentrations of plasma glucose, NEFA, leptin and progesterone were similar in both the groups. It could be concluded that supplementary feeding of 25% concentrate mixture over and above NRC recommendation improved growth performance, feed conversion ratio and gain in body measurements of Sahiwal heifers.